PROFIT-SHARING WAGE PRACTICES AMONG RICE FIELD WORKERS IN PINRANG: AN ISLAMIC LEGAL ANALYSIS - Anwar, Alfiansyah; Ibrahim, Musdalifa; Rizkyanti, Rizkyanti (istinbath, 2025)
The Islamic wage system is grounded in the value and benefit of a person's labor, emphasizing service and usefulness. In contrast to the capitalist approach, which typically ties wages to the minimum cost of living, this system prioritizes the intrinsic worth of work. This research seeks to demonstrate the Islamic legal perspective on wage practices among rice field workers in Tamansari, Tatae Village, Duampanua District, Pinrang Regency, South Sulawesi. This research employs an interpretative approach, utilizing primary data sourced from landowners and field workers through observation, interviews, and documentation. The data collection methods include observation, interviews, and documentation. The wage system for rice field workers uses various models, such as two-way, three-way, and five-way profit sharing. Each model has different mechanisms regarding the distribution of crop yields and the allocation of responsibility for production costs. Although this practice has been implemented in the local community, some aspects of this model are not fully aligned with the principles of Islamic law, especially regarding justice and risk distribution.